Perbandingan Pengaruh Latihan Fartlek Dengan Latihan Sirkuit Training Terhadap Kapasitas Kerja Maksimal VO2 Max Pada Siswa MAN 1 Makassar. - Herman Herman; Muhammad Akbar Syafruddin (Universitas PGRI Semarang, 2021)
This research is a descriptive study to determine (1) the effect of fartlek training on maximal working capacity of VO2 Max in MAN 1 Makassar (2) to determine the circuit training exercise on maximal working capacity of VO2 Max in MAN 1 Makassar (3) to determine differences in the effect of fartlek training with circuit training exercise on maximal working capacity of VO2 Max in MAN 2 Makassar. Population in this study were all students of MAN 1 Makassar while the sample in this study 40 students of class XI were taken by random sampling. The results of this study were (1) the data maximal work capacity (VO2max) through the end of the exercise test farlek obtained an average value of 40,872, a standard deviation of 5.6633, 29.8 minimum value, maximum value of 50.8, and 1634.9 total value of 35 samples (2) Data maximal work capacity (VO2max) obtained an average value of 44.562, a standard deviation of 21.575, 35.4 minimum value, maximum value of 52.2, and 1782.5 total value of 35 samples. Keywords: Effect of exercise training; Fartlek Training; circuit training; VO2Max.Abstrak Jenis penelitian ini adalah penelitian diskriptif untuk mengetahui (1) pengaruh latihan fartlek terhadap kapasitas kerja maksimal VO2 Max pada siswa MAN 1 Makassar (2) untuk mengetahui latihan circuit training terhadap kapasitas kerja maksimal VO2 Max pada siswa MAN 1 Makassar (3) untuk mengetahui perbedaan pengaruh latihan fartlek dengan latihan circuit training terhadap kapasitas kerja maksimal VO2 Max pada siswa MAN 1 Makassar. Populasi dalam penelitian ini adalah seluruh Siswa MAN 1 Makassar sedangkan sampel dalam penelitian ini 40 siswa kelas XI diambil dengan secara random sampling. Hasil penelitian ini adalah 1. Ada pengaruh yang signifikan latihan parlek terhadap kemampuan kerja maksimal (V O2 Max) (P < 0,05), 2. Ada pengaruh yang siknifikan latihan sirkuit terhadap kemampuan kerja maksimal (V O2 Max) (P < 0,05), 3. Ada perbedaan signifikan latihan parlek dan latihan sirkuit, dan 4. Latihan sirkuit lebih baik meningkatkan kemampuan kerja maksimal daripada latihan parlek (P < 0,05). Kata kunci: Pengaruh latihan; latihan fartlek; latihan circuit; VO 2Max